Peran Perbankan Syariah Terhadap Literasi Keuangan Pada Anak-Anak di Satit Phatnawitya School - Sinanti Roilan; Alfi Amalia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research is conducted to to assess the influenceof Islamic banking on strengthening children’s understanding of finance at Satit Phatnawitya School in Thailand. Employing a qualitative research approach, the study utilized observation and interviews to gather insights. The focus was specifically on the Islamic banking education program implemented in the Kindergarten 2 Firdaus class, which consists of children aged 5 to 7 years. The findings reveal that Islamic banking, particularly the Islamic Bank of Thailand, contributes significantly to presenting financial concepts rooted in Islamic principles, for instance the forbidding of usury and the significance of equitable transactions. Principal activity performed of this program is a savings activity aimed at teaching young children the fundamentals of money management from a tender age. This initiative not only fosters positive saving habits but also familiarizes them with Islamic banking products. While there has been a notable improvement in saving practices, the study highlights the ongoing need to enhance children's understanding of long-term financial planning and halal investment. Ultimately, this research indicates that while Islamic banking contributes significantly to children's financial understanding, there is a necessity for a more structured program that can further strengthen their financial habits and knowledge.